PENGEMBANGAN SISTEM PENILAIAN KINERJA BERBASIS KECERDASAN BUATAN - Sopardo Marbun; Haris Abu Bakar Sidik; Wawan Oktriawan; Okto Kurnia (Jurnal Komputer dan Teknologi, 2026)
These days, the creation of AI-Based Performance Appraisal Systems combines the use of more sophisticated data science with best practices in performance management.  This method is therefore broken down into a number of important approaches. In general, the approach entails creating a hybrid system that prioritizes human oversight and prudent managerial decision-making while automating data collection and improving the objectivity of AI-assisted analysis. In order to move away from discrete and subjective evaluation techniques and toward a more effective, flexible, and data-driven performance management system—where each choice is supported by extensive supporting data—AI-based performance appraisal systems are being developed.